Solvatochromism of dye-labeled dendronized polymers of generation numbers 1–4: comparison to dendrimers - Gstrein, Chiara (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Two series of dendronized polymers (DPs) of generations g = 1–4 with different levels of dendritic substitution (low and high) and a solvatochromic probe at g = 1 level are used to study their swelling behavior in a collection of solvents largely differing in polarity as indicated by the Kamlet–Taft parameters. This is done by measuring the UV-Vis spectra of all samples in all solvents and determining the longest wavelength absorptions (λ(max)). The λ(max) values fall into a range defined by the extreme situations, when the solvatochromic probe is either fully surrounded by solvent or completely shielded against it. The former situation is achieved in a model compound and the latter situation is believed to be reached when in a poor solvent the dendritic shell around the backbone is fully collapsed. We observe that solvent penetration into the interior of the DPs decreases with increasing g and does so faster for the more highly dendritically substituted series than for the less highly substituted one. Interestingly, the swelling of the more highly substituted DP series already at the g = 4 level has decreased to approximately 20% of that at the g = 1 level which supports an earlier proposal that high g DPs can be viewed as nano-sized molecular objects. Furthermore, when comparing these two DP series with a g = 1–6 series of dendrimers investigated by Fréchet et al. it becomes evident that even the less substituted series of DPs is much less responsive to solvent changes as assessed by the solvatochromic probe than the dendrimers, suggesting the branches around the (polymeric) core in DPs to be more densely packed compared to those in dendrimers, thus, establishing a key difference between these two dendritic macromolecules.